A clinicopathological study of rhinosporidiosis in a tertiary care hospital - Shariff, Mudassar A. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2018)
Background: Rhinosporidiosis is a chronic granulomatous infective disorder that is caused by Rhinosporidium seeberi. It usually presents as a soft polypoidal, pedunculated or sessile mass arising from the nasal mucosa. Common sites of occurrence of rhinosporidiosis are nasal cavity and nasopharynx, it can also be found in conjunctiva, larynx and maxillary sinuses. Methods: A cross-sectional study was conducted in the outpatient department of ENT, at Vinayaka Mission’s Medical College and Hospital for a period of 1 year 7 months from October 2011 to April 2013. During the study period, all cases that were diagnosed as rhinosporidiosis by histopathology were included in the study group. The aim of this study is to determine the epidemiology, risk factors, clinical features and evaluation of blood group in patients with rhinosporidiosis in a study group. Results: Majority of patients in our study were young male adults from low socio-economic strata and from rural area. The common sites involved were the nasal cavity and nasopharynx. It showed an association with blood group O type. Conclusions: Rhinosporidiosis is an infective disease which is seen in individuals using surface water sources for daily needs. It requires careful clinical evaluation and diagnosis. Patients in high risk group with suspicion should undergo surgical excision with electrocautery. Careful follow up is essential for early diagnosis of recurrence.